2022
DOI: 10.3390/ijerph19105886
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Cyberbullying: Feeling Loneliness and Depression among Youth and Adult Chileans during the Pandemic

Abstract: In Chile, during the COVID-19 pandemic, reports of cyberbullying victimization increased for adolescents and younger adults. Research has shown that cyber-victims—adolescents and young adults alike—are at greater risk for mental health problems such as depression as a result of this negative type of aggression. Yet, a paucity of research has examined the individual mechanisms germane to cyber-victim depression. We focused on loneliness for the current study. We hypothesized that cyber-victimization would be po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Moreover, Alheneidi et al (2021) found that individuals who spent more hours online felt lonely. This loneliness risks the prevalence of individuals engaged in cyberbullying victimization (Olenik-Shemesh et al, 2012;Varela et al, 2022). These results suggest that PIU harms victims, particularly regarding the amount of time spent.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, Alheneidi et al (2021) found that individuals who spent more hours online felt lonely. This loneliness risks the prevalence of individuals engaged in cyberbullying victimization (Olenik-Shemesh et al, 2012;Varela et al, 2022). These results suggest that PIU harms victims, particularly regarding the amount of time spent.…”
Section: Discussionmentioning
confidence: 88%
“…Twenty-six articles were excluded due to not meeting the inclusion criteria: two studies focused on wrong outcomes [64,65], ten were conducted before the COVID-19 pandemic [66][67][68][69][70][71][72][73][74][75], seven articles involved participants aged > 18 years [51,[76][77][78][79][80][81], two articles included participants aged > 18 years and examined the phenomenon before the COVID-19 pandemic [82,83], three did not report the period of data collection nor made any reference to the COVID-19 pandemic [84][85][86], and two studies were no empirical investigations, being a scoping review [87] and a systematic review [88] (Supplementary material, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, three studies documented psychological stress, stress, and acute stress response related to the COVID-19 pandemic as risk factors for cyberbullying perpetration (Barlett et al, 2021; T. Zhang et al, 2022; Zhang et al, 2021), and two studies demonstrated that loneliness contributed to more cyberbullying victimization (Han et al, 2021; Varela et al, 2022). Additionally, one study found that self-rated health was negatively correlated with cyberbullying victimization (T.…”
Section: Resultsmentioning
confidence: 99%
“…Although 21 studies applied validated scales or questionnaires (n = 18), these scales or questionnaires were not unified. Among these studies, Cyberbullying Scale (Yang, 2021;Yang et al, 2022), Olweus Bully/Victim Questionnaire (Vaillancourt et al, 2021;, European Cyberbullying Intervention Project Questionnaire (Maftei et al, 2022;Vejmelka & Matković, 2021), Cyberbullying Questionnaire (Oksanen et al, 2020(Oksanen et al, , 2021, Cyberbullying Experiences Survey (Barlett, Rinker, et al, 2021;Barlett, Simmers, et al, 2021), and Cyberbullying and Online Aggression Survey (Lee et al, 2022;Varela et al, 2022) were used more frequently. The other 12 studies employed twelve different instruments to measure cyberbullying.…”
Section: Study Characteristicmentioning
confidence: 99%
See 1 more Smart Citation